Activity of meropenem/vaborbactam and comparators against Gram-negative isolates from Eastern and Western European patients hospitalized with pneumonia including ventilator-associated pneumonia (2014–19). (23rd July 2021) - Shortridge, Dee; Carvalhaes, Cecilia; Deshpande, Lalitagauri; Castanheira, Mariana
Abstract: Objectives: Meropenem/vaborbactam has been approved in Europe for the treatment of hospital-acquired bacterial pneumonia, ventilator-associated pneumonia (VAP) and bacteraemia among other indications. Vaborbactam is an inhibitor of class A and C β-lactamases, including Klebsiella pneumoniae carbapenemase (KPC) enzymes, but not class B or D carbapenemases. We analysed the activity of meropenem/vaborbactam and comparators against 6846 Enterobacterales and 3567 Pseudomonas aeruginosa isolates from patients hospitalized with pneumonia (PHP), including VAP. Methods: Isolates from PHP were consecutively collected during 2014–19 from 42 European hospitals located in 21 countries and susceptibility tested using the broth microdilution method. Carbapenem-resistant Enterobacterales (CRE) isolates were molecularly characterized to identify their carbapenem-resistance mechanisms. EUCAST (2020) interpretive criteria were used. Results: The most common Gram-negative pathogens isolated from PHP were P. aeruginosa ( n = 3567), K. pneumoniae ( n = 1877) and Escherichia coli ( n = 1646). Overall, 98.0% of Enterobacterales and 82.1% of P. aeruginosa were susceptible to meropenem/vaborbactam, with 99.8% of Enterobacterales and 89.7% of P. aeruginosa in Western Europe (WE) and 92.7% of Enterobacterales and 69.1% of P. aeruginosa in Eastern Europe (EE). CRE were more common in EE (15.1%) than WE (2.1%). KPC was the most common carbapenemase in WE, while OXA-48-like was the most common carbapenemase in EE. Meropenem/vaborbactam susceptibility was 63.0% for all CRE (92.2% in WE and 51.5% in EE). Meropenem/vaborbactam inhibited 99.1% of KPC-producing isolates and 40.5% of OXA-48-like-producing isolates. Conclusions: These in vitro data demonstrate that meropenem/vaborbactam has potent activity against isolates from PHP, including isolates producing KPC, and may be a useful treatment option for PHP, including VAP.